TEKNIK DAN EVALUASI TERJEMAHAN KALIMAT IMPERATIF PADA KITAB AL-FATḤU AR-RABBĀNĪ WAL-FAIḌU AR-RAḤMĀNĪ KARYA ABDUL QADIR AL-JAILANI - Fitria Sari Yunianti; Fitra Nanda (An-Nahdah Al-'Arabiyah, 2023)
This study aims to explain the techniques and assessment of the quality of the translation of imperative sentences in the book Al-Fatḥu Ar-Rabbānī Wal-Faiḍu Ar-Raḥmānī by Sheikh Abdul Qadir Al-Jaelani. This research is a part of translation criticism using the descriptive analysis method. This study uses a qualitative approach to analyzing translation techniques using Newmark's theory. In addition, a quantitative approach is also used in assessing the quality of translation by using the translation evaluation theory by Nababan. The results of this study indicate that there are 977 imperative sentence data and the sample data in this study are 50 imperative sentence data. In this study, it was found that there were 8 techniques used in translation from 16 Newmark translation techniques. The eight techniques are the literal translation technique, paraphrasing technique, transposition technique, common translation technique, expansion technique, synonymy technique, modulation technique, and reduction technique. In addition, the three highest acceptability qualities are literal translation technique, expansion technique, and modulation technique as much as 68%, while the lowest acceptability quality is synonymy technique as much as 56%. Then the readability quality with the highest score is in the literal translation technique and the transposition technique as much as 68%. At the same time, the readability quality with the lowest value is in the paraphrasing technique and the synonymy technique as much as 56%.